The role of science and technology parks in increasing the competitiveness of small and medium sized companies - Marciniec, Berenika M. (Economics and Business Review, 2007)
An increase in competitiveness of an enterprise often results from implementing a new technological solution. If a company wants to remain competitive, it needs to launch new or improved products or services on a continuous basis and to adopt new technologies or procedures which provide more efficient production methods or working practices. The places for developing new technologies in the whole world are science parks. In highly developed countries, these institutions have managed to obtain a stable position in the science technology-economy chain. This paper gives an idea about the role of science and technology parks in modern, knowledge-based economies and such parks' influence on increasing the competitiveness and innovativeness of small and medium sized companies. (original abstract)